Vienna buildings - Unknown:::Creator::::::::::::; Lübke, Wilhelm, 1826-1883 (author):::Contributor::::::::::::; Lützow, Karl von, 1832–1897 (author):::Contributor:::::::::::: (Germany; Paul Neff; Stuttgart)
Engraving of six buildings in Vienna (with layouts and scales), with the following captions: Gebäude der Gesellscheft de Musikfreunde (Hansen), Kirche in Fünfhaus bei Wien (Schmidt), Artchitekien- und Ingenieur-Verein (Thienemann), Chemisches Laboratorium (Ferstel), Weltausstellungs-Gebäude (Hasenauer), Oesterreichisches Museum (Ferstel)